2007
DOI: 10.1016/j.cbi.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Physiological levels of tea catechins increase cellular lipid antioxidant activity of vitamin C and vitamin E in human intestinal Caco-2 cells

Abstract: Oxidative stress has been linked to the development of various chronic diseases. Vegetables and fruits, which contain polyphenols, were shown to have protective effects. (-)-Epigallocatechin-3-gallate (EGCG), a polyphenol abundant in tea, has been shown to have antioxidant activities in cellfree conditions and this study focused on the effect of cellular EGCG. Using an intestinal cell model to examine the oxidative stress induced by hydroxyl radicals, we report here that physiological concentrations (0.1-1 μM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…The synergistic effect of rosemary extract, tocopherol, BHA and AA was observed in the DPPH assay (Romano et al 2009). An additive or synergistic effect was also described for polyphenols and vitamins C and E in preventing lipid oxidation (Murakami et al 2003;Yeomans et al 2005;Intra & Kuo 2007). Significant synergism measured using the DPPH method was also found for four phenolic compounds of 'Ataulfo' mango pulp: chlorogenic, gallic, protocatechuic and vanillic acids.…”
mentioning
confidence: 92%
“…The synergistic effect of rosemary extract, tocopherol, BHA and AA was observed in the DPPH assay (Romano et al 2009). An additive or synergistic effect was also described for polyphenols and vitamins C and E in preventing lipid oxidation (Murakami et al 2003;Yeomans et al 2005;Intra & Kuo 2007). Significant synergism measured using the DPPH method was also found for four phenolic compounds of 'Ataulfo' mango pulp: chlorogenic, gallic, protocatechuic and vanillic acids.…”
mentioning
confidence: 92%
“…On the other hand, tea polyphenols have the ability to participate in vitamin E recycling [11]. Because of the presence of other antioxidant constituents in the green tea extract, it is more stable than pure epigallocatechingallate; one of the major constituents of green tea [12].…”
Section: Introductionmentioning
confidence: 99%
“…A study done to evaluate the relationship between tea catechins and ASC showed that tea catechins have the ability to increase cellular lipid antioxidant activity of vitamin C and vitamin E in human intestinal Caco-2 cells (Intra & Kuo, 2007).…”
Section: Discussionmentioning
confidence: 99%